PENGAPLIKASIAN EDIBLE FILM BERBASIS PATI SINGKONG YANG DIPERKAYA TEPUNG DAUN KELOR PADA PENYIMPANAN BUAH JERUK - Ghaffar, Mufti; Nurhamzah, Lutfi Yulmiftiyanto; Pebrianti, Suci Apsari; Listyawardhani, Yana (Jurnal Teknologi dan Mutu Pangan, 2025)
Various approaches have been developed to address the issue of fruit deterioration during storage, including packaging technology. Among these, the use of edible coatings has gained increasing attention. The method of this study was a laboratory experimental research with a completely randomized design with two replications. This study aimed to evaluate the effectiveness of a cassava starch-based edible coating enriched with moringa leaf flour in preserving the quality and extending the shelf life of citrus fruits during storage at room temperature. The experiment was carried out in three stages: (1) preparation of edible coatings with varying concentrations of moringa leaf flour (0%, 1%, 2%, and 3%), (2) application of the coatings to citrus fruits, and (3) observation of fruit quality over a 21-day storage period. The parameters assessed included weight loss, moisture content, firmness, and sensory attributes such as color, aroma, texture, and flavor. A Completely Randomized Design (CRD) was employed with two replications. The results indicated that the edible coating treatments effectively reduced the rate of physical quality degradation in citrus fruits. In particular, the treatment with 3% moringa leaf flour (F3) resulted in the lowest weight loss and the highest firmness by day 14. Additionally, the peel color of fruits in the F3 treatment remained more stable compared to the control. This study concludes that, although no significant differences were observed in moisture content among the treatments, the application of the edible coating was effective in better preserving the sensory quality of the fruits.